Experts’ content validation of the parosmia, phantosmia, and anosmia test (PARPHAIT): A qualitative study - Annelin Espetvedt; Siri Wiig; Kai Victor Myrnes-Hansen; Daniel Adrian Lungu (PLoS ONE, 2025)
Background The parosmia, phantosmia, and anosmia test (PARPHAIT) has previously been developed as a tool for capturing quantitative and qualitative symptoms of olfactory dysfunction. Its content validity was evaluated in a patient sample, from a statistical point of view through an exploratory factor analysis, and now in a panel of experts. Based on these evaluations, we present the most recent version. The aim of this study was to evaluate the content of the novel PARPHAIT in an expert panel. Methods This was a qualitative interview study with experts in the field of olfaction. The study was done in an international research community on olfactory dysfunction. Thirteen participants (mean age 49.7, 53.8% men) with expertise in the field of smell were interviewed about PARPHAIT’s content, format, and applicability. Participants were selected based on their experience in the field of smell and invited to a digital interview. Results Suggested improvements of PARPHAIT were provided and evaluated. Alterations were done to the formulation of items and introductory text (i.e., instructions and definitions), as well as aspects covered, and the structure and design of the questionnaire. Conclusions PARPHAIT was considered a clear, user-friendly tool suitable for a clinical assessment context. Improvements were made based on experts’ feedback, leading to a final version of the tool. However, some aspects of PARPHAIT remain open for consideration (e.g., response and scoring design) and more work remains to reach consensus on how the PARPHAIT best can capture symptoms of olfactory dysfunction.